Yes of course just text me
M2p÷3
3(2)(6)÷3
3 (2)=6
6 (6)÷3
6×6=36
36÷3=12
The expression m2p÷3 equals 12
Answer:
![\displaystyle \sin\theta=\frac{12}{13}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Csin%5Ctheta%3D%5Cfrac%7B12%7D%7B13%7D)
Step-by-step explanation:
Recall that in a right triangle, sine is the ratio of the opposite side to the hypotenuse:
![\displaystyle \sin\theta=\frac{\text{opposite}}{\text{hypotenuse}}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Csin%5Ctheta%3D%5Cfrac%7B%5Ctext%7Bopposite%7D%7D%7B%5Ctext%7Bhypotenuse%7D%7D)
We are actually not given the opposite side in this case. However, since we know the hypotenuse and the adjacent side, we can use the Pythagorean Theorem to find the opposite side. So:
![a^2+b^2=c^2](https://tex.z-dn.net/?f=a%5E2%2Bb%5E2%3Dc%5E2)
Let <em>a</em> be the adjacent side and <em>b</em> be the opposite side. <em>c</em> will be the hypotenuse.
Substitute:
![(5)^2+b^2=(13)^2](https://tex.z-dn.net/?f=%285%29%5E2%2Bb%5E2%3D%2813%29%5E2)
Solve for <em>b: </em>
<em />
<em />
So, the opposite side measures 12.
Then sine will be:
![\displaystyle \sin\theta=\frac{12}{13}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Csin%5Ctheta%3D%5Cfrac%7B12%7D%7B13%7D)
Answer:
d
Step-by-step explanation:
5x -2
Answer choices:
a. 2-5x
b. 3-5 +2x
c. 5x-2x
d. 2x-2+3x
a.
2-5x can be rewritten as -5x+2, which is not the same as 5x-2
b. 3-5 + 2x can be rewritten as -2 + 2x or 2x-2 which is not equivalent to 5x-2
c. 5x-2x is 3x
3x doesn't equal 5x-2
d. 2x+3x-2 = 5x-2
This expression is equivalent to 5x-2